Development of magnesium-doped biphasic calcium phosphate through sol-gel method - Toibah, A. R.; Sopyan, Iis; Abd Shukor, Mohd Hamdi; S., Ramesh (2008)
Calcium phosphate is an interesting material for bone implant applications, as it shows biocompatibility and bioactivity to tissue bone. Among calcium phosphate-based materials, biphasic calcium phosphate (BCP), a mixture of non-resorbable hydroxyapatite (HA) and resorbable tricalcium phosphate (TCP), has shown to possess unique characteristics appropriate for bone replacement. Doping of magnesium ions into BCP will bring biological improvement. Magnesium ion was found to cause the acceleration of nucleation kinetics of bone minerals. Magnesium depletion adversely affects all stages of skeletal metabolism, leading to decrease in osteoblastic activities and bone fragility. Therefore, the incorporation of magnesium ions into the calcium phosphate structure is of great interest for the development of artificial bone implants. Here we present magnesium-doped biphasic calcium phosphate (Mg-BCP) using chemical doping process through a solgel method. Mg-BCP was produced using calcium nitrate tetrahydrate and di-ammonium hydrogen phosphate as the precursors for calcium and phosphorus, respectively. Magnesium nitrate was used as the source of the dopant. An ammoniacal solution of the monomers was heated until a white gel was obtained. The obtained gel was then dried and subsequently subjected to calcinations. The change in physicochemical properties has been evaluated by using XRD, FTIR, TG/DTA, and FESEM. Individual particles are of less than 100 nm in size, spherical shapes and tightly agglomerated. XRD measurement shown that the powder is Mg-doped BCP with 100% purity, and crystallinity increased with increased of Mg content. FTIR spectroscopy measurement also showed that the increment of crystallinity is directly proportional to the amount of dopant leading to the conclusion that magnesium acts as a sintering additive. This result is in good agreement with the analysis of FESEM where the particles of the Mgdoped BCP are larger as the amount of dopant increased as a result of more progressive fusion of particles.